Lithium-sulfur battery positive electrode material and preparation method thereof

The sulfur positive electrode composite material with a polydopamine film coated with sulfur/porous carbon and formed a core-shell structure, the problem of insufficient rate performance and cycle life of lithium sulfur batteries is solved, and the improvement of high energy density and large-rate performance is achieved, which is suitable for industrialization application.

CN119480956APending Publication Date: 2025-02-18BEIJING QICHEN ZUKAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411499077.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The poor rate performance and cycle life of lithium-sulfur batteries lead to poor performance in high energy density and large-scale applications.

Method used

The polydopamine film layer is coated with sulfur/porous carbon, and elemental sulfur is allowed to enter the micromesoporous porous carbon to form a sulfur positive electrode composite material with a core-shell structure. This method uses porous carbon to improve the electron conductivity of sulfur, departed partially functionalized polydopamine to improve the ion and electron conductivity of sulfur, and inhibits the dissolution and diffusion of polysulfides through physical barriers and chemical coordination of the polydopamine film layer. .

Benefits of technology

It significantly improves the rate performance and cycle life of lithium-sulfur batteries, enhances the battery capacity retention rate and Coulomb efficiency, and is suitable for large-scale production and industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480956A_ABST
    Figure CN119480956A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: coating sulfur / porous carbon with a polydopamine film layer, enabling elemental sulfur to enter micro-mesopores of the porous carbon so as to generate gaps between the polydopamine coating layer and the sulfur / porous carbon, and simultaneously removing part of functional groups on polydopamine, so that the sulfur / porous carbon is prepared. Therefore, the sulfur positive electrode composite material with the core-shell structure is obtained. According to the invention, the electronic conductivity of elemental sulfur is improved by utilizing porous carbon, and the rate capability of the lithium-sulfur battery is improved; the ion and electron conductivity of elemental sulfur is improved by utilizing polydopamine subjected to partial functionalization removal, so that the rate capability of the lithium-sulfur battery is further improved; a gap is formed between the polydopamine coating layer and the sulfur / porous carbon, so that the volume expansion of sulfur can be relieved, and the capacity retention ratio of the lithium-sulfur battery can be improved; and the polydopamine film layer effectively inhibits a shuttle effect caused by dissolution and diffusion of polysulfide through a synergistic effect of physical blocking and chemical coordination, so that the capacity retention ratio of the lithium-sulfur battery is increased, and the cycle life of the lithium-sulfur battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium-sulfur battery positive electrode material and also to a method for preparing the lithium-sulfur battery positive electrode material, belonging to the technical field of energy storage. Background Art

[0002] With the rapid development of related industries such as drones and electric vehicles, the market demand for high-rate and high-energy-density batteries (≥350wh / kg) is becoming increasingly strong. However, traditional battery materials have already approached their theoretical capacity and cannot meet the further development requirements of the market. Therefore, the development of new lithium-ion secondary batteries with high performance, low cost and environmental friendliness is of great strategic significance.

[0003] Elemental sulfur has high theoretical specific capacity (1675mAh / g) and theoretical specific energy (2600Wh / kg), as well as abundant reserves, low price, and environmental friendliness. Lithium-sulfur batteries are considered to be one of the most popular battery systems that will first reach an energy density of more than 500Wh / kg. However, elemental sulfur itself has poor conductivity (at room temperature of 25 degrees Celsius, the conductivity is only 5×10 -30 S / cm), and the polysulfides formed with lithium ions during the charge and discharge process are easily soluble in the organic electrolyte, resulting in the poor cycle performance, low specific capacity, and poor rate performance of lithium-sulfur batteries constructed with elemental sulfur as the positive electrode, thus restricting the further marketization of lithium-sulfur batteries.

[0004] At present, many scientific research institutions and enterprises at home and abroad are committed to the research and development of lithium-sulfur batteries. The commonly used methods are to improve the utilization rate of sulfur through conductive materials, use catalysts to improve the conversion efficiency of sulfur, use porous materials to fix and adsorb polysulfides, use chemical bonds and polysulfides to coordinate, and use the physical and chemical barrier effects of coatings and functional diaphragms to reduce the "shuttle effect" of lithium-sulfur batteries and improve the discharge capacity and cycle life of lithium-sulfur batteries. Although these methods have achieved good results, there are relatively few preparation methods that can be mass-produced, have good reproducibility, excellent electrochemical properties and low cost. This is the main problem currently facing lithium-sulfur batteries. If they want to occupy a place in the future energy field, they also need to develop lithium-sulfur battery positive electrode materials that are easy to industrialize and have excellent electrochemical properties. Summary of the invention

[0005] The first object of the present invention is to provide a lithium-sulfur battery positive electrode material that improves the rate performance and cycle life of the lithium-sulfur battery.

[0006] The first object of the present invention is achieved through the following technical measures: a lithium-sulfur battery positive electrode material, characterized in that it is a sulfur / porous carbon coated with a polydopamine film layer, and then the elemental sulfur enters the micropores of the porous carbon to generate gaps between the polydopamine coating layer and the sulfur / porous carbon, and at the same time, some functional groups on the polydopamine are removed to form a partially defunctionalized polydopamine coating layer, thereby obtaining a sulfur positive electrode composite material with a core-shell structure.

[0007] The present invention utilizes porous carbon to improve the electronic conductivity of elemental sulfur, thereby improving the rate performance of a lithium-sulfur battery; utilizes partially defunctionalized polydopamine to improve the ionic and electronic conductivity of elemental sulfur, thereby further improving the rate performance of a lithium-sulfur battery; generates gaps between the polydopamine coating layer and the sulfur / porous carbon, thereby relieving the volume expansion of sulfur and improving the capacity retention rate of the lithium-sulfur battery; and the polydopamine film layer effectively inhibits the "shuttle effect" caused by the dissolution and diffusion of polysulfides through the synergistic effect of physical blocking and chemical coordination, thereby improving the capacity retention rate and cycle life of the lithium-sulfur battery.

[0008] The present invention firstly completes the coating of sulfur / porous carbon with a polydopamine film layer by a liquid phase method, and then allows elemental sulfur to enter the micro-mesopores of the porous carbon by a molten salt method.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned lithium-sulfur battery positive electrode material.

[0010] The second object of the present invention is achieved by the following technical measures: A method for preparing the above-mentioned lithium-sulfur battery positive electrode material, characterized in that it includes the following steps:

[0011] S1, putting sulfur powder and porous carbon into a ball mill for ball milling;

[0012] S2, adding the ball-milled sulfur / porous carbon mixture to an aqueous solution containing dopamine and stirring, filtering, washing, and vacuum drying after the reaction is completed to obtain a polydopamine-coated sulfur / porous carbon composite material;

[0013] S3. Put the polydopamine-coated sulfur / porous carbon composite material into a reactor, introduce protective gas, and then put the reactor into a constant temperature box for molten salt method treatment. After the reaction is completed, the lithium-sulfur battery positive electrode material can be obtained.

[0014] In the step S1 of the present invention, the ball milling rate is 300 to 600 rpm, and the ball milling time is 60 to 300 minutes.

[0015] In the present invention, in step S2, stirring is performed for 2 to 6 hours.

[0016] In the step S3 of the present invention, the reaction temperature is 100-200° C., the heating rate is 0.1-0.5° C. / min, and the insulation time after reaching the reaction temperature is 1-10 hours.

[0017] The porous carbon described in the present invention is mesoporous carbon, Ketjen black or activated carbon, and the pore size is 2-100nm.

[0018] The mass ratio of the sulfur powder to the porous carbon of the present invention is 1:1 to 4:1.

[0019] In the step S2 of the present invention, the concentration of the dopamine solution is 0.01-0.2 M / L, the pH value of the solution is 8.0-9.0, and the reaction temperature is 25-60°C.

[0020] Compared with the prior art, the present invention has the following significant effects:

[0021] ⑴ The present invention utilizes porous carbon to improve the electronic conductivity of elemental sulfur and enhances the rate performance of lithium-sulfur batteries; utilizes partially defunctionalized polydopamine to improve the ionic and electronic conductivity of elemental sulfur and further enhances the rate performance of lithium-sulfur batteries; generates gaps between the polydopamine coating layer and the sulfur / porous carbon, which is beneficial to alleviate the volume expansion of sulfur and enhance the capacity retention rate of lithium-sulfur batteries; the polydopamine film layer effectively inhibits the "shuttle effect" caused by the dissolution and diffusion of polysulfides through the synergistic effect of physical blocking and chemical coordination, thereby enhancing the capacity retention rate and cycle life of lithium-sulfur batteries.

[0022] ⑵ The present invention can obtain the required partially functionalized polydopamine-coated sulfur / porous carbon composite material with a core-shell structure by combining a simple liquid phase method and a molten salt method. The preparation method is simple, the operation is convenient, and it is suitable for large-scale production, which plays a certain role in promoting the industrial application of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0024] Figure 1 It is a schematic diagram of the preparation process of the positive electrode material of the lithium-sulfur battery of the present invention;

[0025] Figure 2 This is a cycle performance diagram of the polydopamine-coated sulfur / ketjen black composite material as the positive electrode at a rate of 0.2C in Comparative Example 1;

[0026] Figure 3 This is a cycling performance diagram of the partially defunctionalized polydopamine-coated sulfur / ketjen black composite material as a positive electrode at a rate of 0.2C in Example 1 of the present invention.

[0027] In the figure: 1-porous carbon, 2-polydopamine coating layer, 3-elemental sulfur, 4-micro-mesopores, 5-partially defunctionalized polydopamine coating layer, 6-voids. DETAILED DESCRIPTION

[0028] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the protection scope of the present invention.

[0029] like Figure 1 As shown, it is a lithium-sulfur battery positive electrode material of the present invention, which is completed by a liquid phase method to coat the sulfur / porous carbon with a polydopamine film layer 2, and then the elemental sulfur 3 is allowed to enter the micropores 4 of the porous carbon 1 by a molten salt method to generate gaps 6 between the polydopamine coating layer and the sulfur / porous carbon, and at the same time, some functional groups on the polydopamine are removed to form a partially defunctionalized polydopamine coating layer 5, thereby obtaining a sulfur positive electrode composite material with a core-shell structure.

[0030] The preparation method of the above-mentioned lithium-sulfur battery positive electrode material is a combination of a conventional liquid phase method and a molten salt method.

[0031] The principle of the present invention is as follows: firstly, polydopamine-coated sulfur / porous carbon is prepared by a liquid phase method, and then sulfur is forced to enter the micropores of the porous carbon by a molten salt method, so that gaps are generated between the polydopamine film layer and the sulfur / porous carbon, which is beneficial to alleviate the problem of positive electrode material falling off from the current collector due to the volume expansion of sulfur, and improve the capacity retention rate of the lithium-sulfur battery; at the same time, part of the functional groups on the polydopamine can be removed, the electronic conductivity of the polydopamine film layer can be improved, thereby improving the ionic and electronic conductivity of elemental sulfur and enhancing the rate performance of the lithium-sulfur battery; the functional groups on the polydopamine film layer can coordinate with polysulfides, reduce the "shuttle effect" caused by the dissolution and diffusion of polysulfides, and at the same time, the coating layer can physically block the dissolution and diffusion of polysulfides, further reduce the "shuttle effect", and improve the capacity retention rate and cycle life of the lithium-sulfur battery.

[0032] Example 1

[0033] Preparation of positive electrode materials for lithium-sulfur batteries:

[0034] Step S1, put 14g of sulfur powder and 6g of Ketjen black into a 500ml ball mill for mixing, the ball milling speed is 500 rpm, and the ball milling time is 60 minutes;

[0035] Step S2, adding the ball-milled sulfur / ketjen black mixture to a dopamine solution with a concentration of 0.016 M / L, the reaction time is 180 minutes, the stirring rate is 300 rpm, the pH value of the solution is 8.2, the solution temperature is 30 degrees, and after the reaction is completed, filtering, washing and vacuum drying at 60 degrees to obtain a polydopamine-coated sulfur / ketjen black complex;

[0036] Step S3, put the polydopamine-coated sulfur / ketjen black complex into a 200 ml reactor, introduce nitrogen and put the reactor into a constant temperature box for molten salt treatment, the heating rate is 0.2 degrees / minute, the temperature is raised to 155 degrees and then kept warm for 5 hours, and after the reaction is completed, a partially functionalized polydopamine-coated sulfur / ketjen black composite material can be obtained.

[0037] Preparation of lithium-sulfur batteries:

[0038] The partially functionalized polydopamine-coated sulfur / ketjen black complex, acetylene black and polyacrylic acid are mixed in a mass ratio of 7.5:1.5:1, and then an appropriate amount of deionized water is added, and then the mixture is ball-milled, wherein the number of revolutions of the ball mill is 300 rpm and the ball-milling time is 6 hours. The ball-milled slurry is evenly applied on the aluminum foil and vacuum dried (drying temperature is 60 degrees Celsius and drying time is 8 hours) as the positive electrode of the lithium-sulfur battery. The negative electrode is a metal lithium sheet, the polypropylene porous membrane is a battery separator, and the electrolyte is DOL+DME (volume ratio is 1:1) containing 1% LiNO3 and a concentration of 1 mol / L LiTFSI. After completing the assembly of the button cell in an argon environment glove box, the battery performance test is carried out on the charge and discharge instrument. The voltage range of the battery test is 1.6V to 2.7V.

[0039] Comparative Example 1

[0040] The difference from Example 1 is that the polydopamine-coated sulfur / ketjen black composite is not subjected to the molten salt treatment in step 3; the rest is the same as Example 1.

[0041] Example 2

[0042] Step S2, the reaction time is 300 minutes, and the reaction temperature is 30 degrees; the other steps are the same as Example 1.

[0043] Example 3

[0044] Step S2, the concentration of the dopamine solution is 0.02M / L, the reaction time is 240 minutes, and the reaction temperature is 40 degrees;

[0045] Step S3, put the complex obtained in step S2 into a 200ml reactor, introduce nitrogen and put the reactor into a constant temperature box for molten salt treatment, the heating rate is 0.1 degrees / minute, the temperature is raised to 180 degrees and then kept warm for 3 hours, and after the reaction is completed, a partially functionalized polydopamine-coated sulfur / ketjen black composite material can be obtained.

[0046] The rest is the same as Example 1.

[0047] Example 4

[0048] Step S1, putting 15 g of sulfur powder and 5 g of Ketjen black into a ball mill, the ball milling speed is 500 rpm, and the ball milling time is 120 minutes;

[0049] Step S2, putting the mixture obtained in step S1 into a dopamine solution with a concentration of 0.03M / L, the reaction time is 120 minutes, and the stirring rate is 500 rpm.

[0050] The rest is the same as Example 1.

[0051] Example 5

[0052] Step S1, put 15g of sulfur powder and 5g of activated carbon into a ball mill, the ball milling speed is 400 rpm, and the ball milling time is 60 minutes;

[0053] Step S2, putting the mixture obtained in step S2 into a dopamine solution with a concentration of 0.02M / L, the reaction time is 180 minutes, the reaction temperature is 25°C, and the solution stirring rate is 300 rpm.

[0054] The rest is the same as Example 1.

[0055] Example 6

[0056] Step 1, put 15g of sulfur powder and 5g of activated carbon into a ball mill, the ball milling speed is 600 rpm, and the ball milling time is 120 minutes;

[0057] Step 3, put the complex obtained in step S2 into a 200ml reactor, introduce nitrogen and put the reactor into a constant temperature box for molten salt treatment, the heating rate is 0.3 degrees / minute, the temperature is raised to 175 degrees and then kept warm for 4 hours, and after the reaction is completed, a partially functionalized polydopamine-coated sulfur / ketjen black composite material can be obtained.

[0058] The rest is the same as Example 1.

[0059] Example 7

[0060] Step S1, put 13g of sulfur powder and 7g of activated carbon into a ball mill, the ball milling speed is 500 rpm, and the ball milling time is 90 minutes;

[0061] Step S2, placing the mixture obtained in step S1 into a dopamine solution with a concentration of 0.021 M / L, reacting for 4 hours at a reaction temperature of 45° C. and stirring the solution at a rate of 500 rpm;

[0062] Step S3, put the complex obtained in step S2 into a 200ml reactor, introduce nitrogen and put the reactor into a constant temperature box for molten salt treatment, the heating rate is 0.2 degrees / minute, the temperature is raised to 180 degrees and then kept warm for 2 hours, and after the reaction is completed, a partially functionalized polydopamine-coated sulfur / ketjen black composite material can be obtained.

[0063] The rest is the same as Example 1.

[0064] Example 8

[0065] Step S1, put 13g of sulfur powder and 7g of activated carbon into a ball mill, the ball milling speed is 500 rpm, and the ball milling time is 90 minutes;

[0066] Step S2, placing the mixture obtained in step S1 into a dopamine solution with a concentration of 0.02 M / L, reacting for 4 hours at a reaction temperature of 35° C. and stirring the solution at a rate of 400 rpm;

[0067] Step S3, putting the complex obtained in step S2 into a 200ml reactor, introducing nitrogen and placing the reactor into a constant temperature box for molten salt treatment, with a heating rate of 0.1 degrees / minute, heating to 200 degrees and keeping warm for 1 hour, and after the reaction is completed, a partially functionalized polydopamine-coated sulfur / ketjen black composite material can be obtained.

[0068] The rest is the same as Example 1.

[0069] Test results

[0070] The test data of electrochemical performance are shown in Table 1:

[0071]

[0072]

[0073] (Table 1)

[0074] From the results of Examples 1 to 8 and Comparative Example 1, it can be seen that Comparative Example 1 (such as Figure 2As shown in Example 1 (as shown in Example 2), the first cycle discharge capacity at 0.2C rate is 931.2 mAh / g, the capacity retention rate after 100 cycles is 76.7%, and the coulombic efficiency is 96.5%. Figure 3 As shown in the figure, the initial discharge capacity at 0.2C rate is 1040.1mAh / g, the capacity retention rate after 100 cycles is 89.5%, and the coulombic efficiency is 98.1%. Similarly, compared with Examples 2 to 8, the discharge capacity of Comparative Example 1 at 0.2C rate is 35.8mAh / g to 142.6mAh / g lower, the coulombic efficiency is reduced by 0.9% to 2.1%, and the capacity retention rate is 11.3% to 16.1% lower. In addition, at 0.05C rate, the initial discharge capacity of Comparative Example 1 and Example 1 are 1398.1mAh / g and 1414.8mAh / g, respectively. It can be seen that when the discharge rate is small, the initial discharge capacity of the two is not much different. As the rate increases, the difference in discharge capacity also gradually increases. Because the migration rate of ions and electrons increases with the increase in rate, higher requirements are also placed on the electronic and ionic conductivity of the material itself. It can be seen from the test results of the embodiments and comparative examples that the partially functionalized polydopamine film layer significantly improves the electronic conductivity and increases the discharge capacity of the lithium-sulfur battery; while the core-shell structure is conducive to alleviating the volume expansion of elemental sulfur and maintaining the integrity of the coating layer, thereby reducing the "shuttle effect" and improving the capacity retention rate and coulomb efficiency of the lithium-sulfur battery. The synergistic effect of the partially functionalized polydopamine film layer obtained by first coating and then molten salt method and the core-shell structure effectively improves the rate performance and cycle life of the lithium-sulfur battery, and the effect will become more obvious as the number of cycles increases.

[0075] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A positive electrode material for a lithium-sulfur battery, characterized in that: It is achieved by coating sulfur / porous carbon with a polydopamine film layer, allowing elemental sulfur to enter the micropores of the porous carbon to create gaps between the polydopamine coating layer and the sulfur / porous carbon, and simultaneously removing some functional groups on the polydopamine to form a partially defunctionalized polydopamine coating layer, thereby obtaining a sulfur positive electrode composite material with a core-shell structure.

2. The lithium-sulfur battery positive electrode material according to claim 1, characterized in that: First, the polydopamine film is coated on the sulfur / porous carbon by a liquid phase method, and then the elemental sulfur is introduced into the micropores of the porous carbon by a molten salt method.

3. A method for preparing the positive electrode material for a lithium-sulfur battery according to claim 1 or 2, characterized in that The following steps are involved: S1, putting sulfur powder and porous carbon into a ball mill for ball milling; S2, adding the ball-milled sulfur / porous carbon mixture to an aqueous solution containing dopamine and stirring, filtering, washing, and vacuum drying after the reaction is completed to obtain a polydopamine-coated sulfur / porous carbon composite material; S3. Put the polydopamine-coated sulfur / porous carbon composite material into a reactor, introduce protective gas, and then put the reactor into a constant temperature box for molten salt method treatment. After the reaction is completed, the lithium-sulfur battery positive electrode material can be obtained.

4. The preparation method according to claim 3, characterized in that: In the step S1, the ball milling rate is 300-600 rpm, and the ball milling time is 60-300 minutes.

5. The preparation method according to claim 4, characterized in that: In the step S2, stirring is performed for 2 to 6 hours.

6. The preparation method according to claim 5, characterized in that: In step S3, the reaction temperature is 100-200° C., the heating rate is 0.1-0.5° C. / min, and the insulation time after reaching the reaction temperature is 1-10 hours.

7. The preparation method according to claim 6, characterized in that: The porous carbon is mesoporous carbon, Ketjen black or activated carbon, and the pore size is 2-100 nm.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the sulfur powder to the porous carbon is 1:1 to 4:

1.

9. The preparation method according to claim 8, characterized in that: In step S2, the concentration of the dopamine solution is 0.01-0.2 M / L, the pH value of the solution is 8.0-9.0, and the reaction temperature is 25-60°C.